One-year experience in carotid endarterectomy combining general anaesthesia with preserved consciousness and sequential carotid cross-clamping - Ucci, Alessandro; D'Ospina, Rita Maria; Fanelli, Mara; Rossi, Giulia; Persi, Federica; Bridelli, Franca; Tosi, Michela; Bianchini Massoni, Claudio; Perini, Paolo; Nabulsi, Bilal; de Troia, Alessandro; Tecchio, Tiziano; et al. (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: We report 1-year single-centre experience in carotid endarterectomy (CEA) combining general anaesthesia with preserved consciousness (GAPC) and standardized carotid sequential cross-clamping, for our protocol effectiveness evaluation in reduction of perioperative stroke, death or cardiologic complications. Methods: We considered all patients who underwent CEA in 2016. All patients underwent superficial cervical plexus block and GAPC with Remifentanil. The surgical technique consisted of common carotid artery (CCA) cross-clamping, carotid bifurcation isolation, external (ECA) and internal carotid artery (ICA) cross-clamping. After CCA cross-clamping, we performed a neurological tolerance test (NTT); this allowed selective shunting only for positive NTT. Primary end-points were: transient ischemic attack (TIA)/stroke, myocardial infarction, death in perioperative period. Secondary end-points were: carotid shunting, peripheral cranial nerves injuries (PCNI), GAPC intolerance, other complications, reintervention in perioperative period, length of hospital stay. Results: 104 consecutive patients underwent CEA with this protocol in the considered period. Twenty-seven (25.9%) patients were symptomatic. Mean clamping time was 48±13.5 minutes. Five cases (4.8%) requested internal carotid artery shunting. No TIA/stroke, myocardial infarction or death were recorded in the perioperative period. PCNI were observed in 19 cases (18.2%) in the immediate post-operative period; 16 of them (84.2%) showed complete or partial resolution at discharge. Only one patient (0.9%) showed GAPC intolerance. No other complication occurred. Three patients (2.9%) underwent reintervention for neck haematoma drainage. Mean hospital stay were 3±0.9 days. Conclusions: GAPC associated with sequential carotid cross-clamping appeared to be safe and effective in prevention of major neurological and cardiologic complications during CEA.